The involvement of maladaptive schemas in intimate partner violence and psychological well-being: A descriptive review of literature - Quiñon Acero, Anyela Milagros (2022)
The objective of this study was to analyze the available literature on maladaptive patterns in intimate partner violence and psychological well-being, from the descriptive review of the literature; for this purpose, a search was conducted in EBSCOhost, Scielo, Scopus, ProQuest and Science Direct, considering the search terms “schemes”, “violence”, “psychological well-being” and “health” mental. More than 20 full-text papers were reviewed, from which 16 academic papers published in Spanish, Portuguese or English between 2015 and 2021 were selected; the results show that people with maladaptive schemes have patterns that compromise their memories, body sensations, emotions and cognitions about themselves and their relationships with others. Likewise, the symptoms of depression were associated with the domain of disconnection and rejection; which is also associated as a predictor of violence; autonomy and performance, these three schemes associated with psychopathological symptoms; it is concluded that the maladaptive schemes are related to harmful experiences in childhood. Early intervention and prevention measures are needed, especially for those who have experienced violence in their homes prioritizing psychological well-being and not becoming a risk factor.